Accumulation and effect of contaminants in soil biota following waste stream application in agriculture: A European perspective - Iris L. Schaap; Marjolein Derks; Peter W.G. Groot Koerkamp; Nico W. van den Brink (Geoderma)
The global food system is under significant pressure from challenges like resource depletion, climate change, and population growth, which drive a heightened demand for food production in conflict with unsustainable methods. Circular agriculture aims to mitigate these challenges by minimizing waste. A promising approach involves utilizing waste as biofertilizers, but this raises concerns about the safety of contaminants such as chemicals, plastics, and pathogens present in waste streams. Soil health, vital for agriculture, faces potential risks from these contaminants. This review examines the accumulation and hazards of waste stream contaminants on soil biota, addressing knowledge gaps and advancing strategies for robust risk assessment based on European studies. Findings reveal a notable disparity between emerging contaminants detected in waste streams and their limited presence in soil organisms. Correlations between bioaccumulation and sub-lethal effects across species, contaminants, and waste streams are sparse, reflecting critical gaps in understanding. In particular, behavioural changes in soil organisms, which significantly influence soil functionality and ecosystem processes, remain underexplored. To address these gaps, an ecological perspective that considers the roles of diverse soil species is crucial. Earthworms, with their sensitivity to toxic stress (avoidance behaviour) and ecological functions (bioturbation), are highlighted as essential bioindicators. Evaluating their responses to waste stream applications offers insights into soil toxicity and fertility. By balancing toxic stress with the potential benefits of waste utilization under specific environmental conditions, this approach aims to enhance soil health while supporting sustainable agricultural practices.